2015
DOI: 10.1371/journal.pone.0127574
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone, Cognitive Function and Dementia: A Systematic Review

Abstract: BackgroundMetabolic factors are increasingly recognized to play an important role in the pathogenesis of Alzheimer’s disease and dementia. Abnormal parathyroid hormone (PTH) levels play a role in neuronal calcium dysregulation, hypoperfusion and disrupted neuronal signaling. Some studies support a significant link between PTH levels and dementia whereas others do not.MethodsWe conducted a systematic review through January 2014 to evaluate the association between PTH and parathyroid conditions, cognitive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 45 publications
0
50
2
7
Order By: Relevance
“…Higher incidence of anxiety, depression, and overall reduced quality of life occurs in patients with hypoparathyroidism compared to normal control groups (8, 25, 26). However, one systematic review failed to show a link between PTH and cognitive dysfunction and dementia (27), so it is assumed that these conditions are mostly due to the calcium disturbance.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Higher incidence of anxiety, depression, and overall reduced quality of life occurs in patients with hypoparathyroidism compared to normal control groups (8, 25, 26). However, one systematic review failed to show a link between PTH and cognitive dysfunction and dementia (27), so it is assumed that these conditions are mostly due to the calcium disturbance.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…As a result, Ocn promotes glucose homeostasis, enhances energy expenditure and prevents the appearance of glucose intolerance induced by high fat diet (Figure 2). Moreover, Ocn favors male reproductive functions in mice by promoting testosterone biosynthesis by the testis, following its binding to a receptor expressed in Leydig cells, Gprc6a, that belongs to the G-protein coupled receptor family [24,[29][30][31]81] (Figure 2). It was also shown that Gprc6a is expressed in pancreatic β-cells and that it is also the receptor mediating Ocn influences on the energy metabolism [32].…”
Section: Bone As An Endocrine Organmentioning
confidence: 99%
“…This makes it unlikely that this receptor transduces Ocn signals in the brain. This last notion is also important because it implies that the passivity of the Ocn-/-mice is not a mere consequence of metabolic or reproductive abnormalities, since these are equally severe in Ocn-/-and Gprc6a-/-mice [24,30,86,87]. Mother-derived osteocalcin crosses the placental barrier from E14.5 until birth and influences brain development by preventing neuronal apoptosis.…”
Section: Osteocalcin and Its Functions In Adult Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Действительно, результа-ты исследований подтвердили более высо-кий уровень тревожности, депрессии и сни-жение качества жизни в данной когорте больных [1,28,29]. Однако в другом систе-матическом обзоре не выявлено корреляции уровня ПТГ с когнитивной дисфункцией и деменцией [30], поэтому вероятнее всего данные нарушения психической функции связаны с гипокальциемией. Кроме того, при гипопаратиреозе повышен риск развития ка-таракты [29], нарушения состояния эмали зубов [31] и кальцификации базальных ган-глиев [1].…”
Section: таблица 1 (окончание)unclassified